2016
DOI: 10.1080/15313204.2016.1146190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Relational Harmony in the Use of Drug-Refusal Strategies of Rural Native Hawaiian Youths

Abstract: This study examined the role of maintaining relational harmony among family members in the use of drug refusal strategies for rural Hawaiian youth. Youth focus groups were conducted to validate refusal strategies used in realistic, hypothetical drug-related problem situations. The findings suggested gender-specific motivations for maintaining relational harmony among family members when faced with drug offers from them. Specifically, boys described instrumental concerns when using refusal strategies (i.e., not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Previous studies have shown the efficacy of teaching refusal and resistance skills to children and youth. 46 , 47 These skills increase children’s knowledge of the adverse effects of drugs and help them resist substance offers from family and friends. 48 , 49 Emphasis should therefore be placed at delaying the age of substance use debut, which is associated with positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the efficacy of teaching refusal and resistance skills to children and youth. 46 , 47 These skills increase children’s knowledge of the adverse effects of drugs and help them resist substance offers from family and friends. 48 , 49 Emphasis should therefore be placed at delaying the age of substance use debut, which is associated with positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research indicated that there was an influence of family harmony to subjective norm. This research was supported by research conducted Bills (2016) indicated that there was influence of family harmony on the use of drugs in Hawaii.…”
Section: Effect Of Behavioral Control Perceptionon Drug Use Through mentioning
confidence: 80%
“…Schafer's research suggests to maintaining harmony in a family, adolescents are forced to accept offers of drug use from their family members. Research showed further that the offer of drug use is very problematic for teenagers and their families (Bills, 2016).…”
Section: Effect Of Behavioral Control Perceptionon Drug Use Through mentioning
confidence: 99%
“…Therefore, the influence of friends and peer pressure 31 may be associated with high-risk behaviors, but friends are preferred in seeking help. 26 , 30 Self-evidently, having family members who use drugs and adverse life events are associated with high risk. 31 , 32 On the other hand, peer networks and dynamic group leaders can also help to motivate the students.…”
Section: Resultsmentioning
confidence: 99%